The absence of the common hepatic artery and its implications for surgical practice: Results of a systematic review and meta-analysis. Issue 3 (June 2019) - Cirocchi, Roberto; D'Andrea, Vito; Lauro, Augusto; Renzi, Claudio; Henry, Brandon Michael; Tomaszewski, Krzysztof Andrzej; Rende, Mario; Lancia, Massimo; Carlini, Luigi; Gioia, Sara; Randolph, Justus
Abstract: Introduction: The common hepatic artery (CHA) is the main arterial supply to the liver. Common classifications of the anatomical variations of the celiac trunk have only marginally described the CHA. Currently, the only classification addressing anatomical variants in cases of CHA absence from the celiac trunk is that reported by Huang et al. In this systematic review, the prevalence of these variations, according to Huang's classification, have been analyzed. Methods: The review was registered in PROSPERO (CRD 42018096679). The risk of bias was assessed using the AQUA tool. Results: Fifty-four articles were included in the review (26, 250 participants). The overall pooled prevalence estimate (PPE) of an absent CHA was 3.1%. Of those participants who underwent preoperative radiological evaluation, the overall PPE of an absent CHA was 3.8% for subjects who were evaluated via angiography and 3.0% for participants who underwent angio-CT evaluation. The overall PPE of an absent CHA was 3.9% in cadavers and 3.2% in participants evaluated surgically. Type I or Type II aberrations were the most common; in participants with CHA aberrations, 65.4% of those participants had either Type I or Type II aberrations. Conclusions: The overall PPE of an absent CHA was 3.1%, a result representing a significant, common anatomical variation. Our study revealed that an absence of a CHA was associated with a replaced CHA. The most common arterial variant was a replaced CHA originating from the Superior Mesenteric Artery and running across the anterior or posterior side of the pancreas (i.e., Types I and II). Highlights: Variations of common hepatic artery strongly affect gastrointestinal surgery. Overall common hepatic artery is absent in 3.1% of patients The absence of the Common Hepatic Artery is associated with a replaced artery The most of the replaced arteries originate from the Superior Mesenteric Artery. A thorough preoperative evaluation is mandatory for the assessment of the surgical anatomy.